Yield performance, adaptability and processing qualities of pre-release potato clones under different Rwandan agro-ecologies - Placide, R.; Theophile, N.; Vandamme, Elke; Nshimiyimana, J.C.; Mendes, T. (Springer, 2022)
Five new potato clones (CIP393280.64, CIP393371.58, CIP393077.159, CIP396018.241, and CIP398190.615) and two local checks (Kinigi and Kirundo) were evaluated in fourteen sites under the National Performance Trials (NPTs) for two growing seasons using a randomized complete block design with three replications to identify their yield performance, adaptability and processing qualities. The data related to yield (number and weight of tubers per plot, marketable and unmarketable yields, and total yields) and processing qualities (tuber shape and depth of eyes, dry matter content, frying time, crisps color, taste, crunch, waste percentage, and conversion rate) were collected and analysed using GenStat 20th edition. The analysis of variance revealed significant effects of clone, site, and clone by site interaction on fresh tuber yield. Across all sites for both seasons, the clones CIP393077.159, CIP393371.58, and CIP393280.64 revealed the yields of 31, 28. and 27 tons/ha that fall in the same range of yields as local checks Kinigi and Kirundo with 30 and 35 tons/ha, respectively. Based on yield stability index (YSI) ranking combining high yield and stability, the first four genotypes were Kirundo, CIP393077.159, CIP39601.241, and CIP393371.58 with YSI of 16.6, 11.3, 9.1, and 7.3, respectively. All the new tested potato clones revealed higher dry matter (DM) content that was above 18% of total fresh weight except CIP396018.241 which had a DM content of 17% of fresh weight. This dry matter content was comparable with the dry matter content of local check Kinigi, the most popular varieties variety used for French fries in Rwanda. Based on crisps color, the clones CIP393077.159, CIP393280.64, CIP396018.241, CIP398190.615 showed the same trend as local check Kinigi. The crisps from these clones were ranked as good or very good for taste and crunch. The results of this study highlighted that the clones CIP393371.58 and CIP393077.159 can be recommended as candidate for new varieties for high fresh tuber yields; while the clones CIP398190.615, CIP396018.241, and CIP393280.64 can be recommended as candidate for new potato varieties for crisps and French fries.